2016
DOI: 10.1097/mpg.0000000000000920
|View full text |Cite
|
Sign up to set email alerts
|

Small Bowel Bacterial Overgrowth in Children

Abstract: Further research is needed to determine the clinical impact of SBBO and to establish diagnostic and therapeutic guidelines applicable to children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 121 publications
2
36
0
5
Order By: Relevance
“…A recently published review noted a high incidence of diarrhea reported in children with SIBO, with abdominal pain, bloating, and flatulence also commonly reported . Diarrhea and bloating have been found to be the most common symptoms in adults with duodenal culture‐proven SIBO .…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…A recently published review noted a high incidence of diarrhea reported in children with SIBO, with abdominal pain, bloating, and flatulence also commonly reported . Diarrhea and bloating have been found to be the most common symptoms in adults with duodenal culture‐proven SIBO .…”
Section: Discussionsupporting
confidence: 58%
“…Small intestinal aspirate and culture are not an appropriate test for children with mild nonspecific symptoms or for those who may need repeated testing due to associated risks (anesthetic/sedation and endoscopy) and is too invasive for most research purposes …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations